Incorporation of proteins with different isoelectric points into biomimetic Ca-P coatings : a new approach to produce hybrid coatings with tailored properties - Azevedo, Helena S. (2006)
This work aims to study the effect of incorporating proteins with different isoelectric points (pI) on the structure, composition and morphology of biomimetic calcium-phosphate (Ca-P) coatings. For that, bovine serum albumin (BSA) and lysozyme, having respectively acidic and basic pIs, were used as model proteins. It was observed that the incorporation of positively charged proteins, such as lysozyme, was able to significantly change the structure of the coatings, possibly due to the preferential interactions between the protein and negatively charged phosphate ions. These results indicated that proteins with different characteristics can be incorporated into biomimetic Ca-P coatings in order to obtain a hybrid coating and at the same tailoring their properties.